Quadripartitioned Neutrosophic Q-Ideals of Q-Algebra (BISTUA Revista de la Facultad de Ciencias Básicas, 2023)
The main aim of this paper is to procure the idea of quadripartitioned neutrosophic Q-ideal (in short QN-Q-I) of quadripartitioned neutrosophic Q-algebra (in short QN-Q-A) as an extension of intuitionistic fuzzy Q-ideal (in short IF-Q-I) of intuitionistic fuzzy Q-algebra (in short IF-Q-A). Besides, we formulate some interesting results on it in the form of remark, theorem, etc. Further, we furnish some suitable examples.
Keywords: QNS; QN-Q-I; QN-Q-Q; Neutrosophic set